2015
DOI: 10.1109/ted.2015.2454953
|View full text |Cite
|
Sign up to set email alerts
|

SiO<sub>2</sub> Free HfO<sub>2</sub> Gate Dielectrics by Physical Vapor Deposition

Abstract: HfO 2 layers, 25-Å thick, were grown by cyclic Hf sputter deposition and room temperature oxidation steps on chemically oxidized Si(001). Subsequent in situ annealing and TiN deposition yield a high-κ gate-stack for which the original 8-Å-thick SiO 2 layer is eliminated, as confirmed by transmission electron microscopy. Transistors fabricated with this gate-stack achieve an equivalent oxide thickness in inversion T inv = 9.7 Å, with a gate leakage J g = 0.8 A/cm 2 . Devices fabricated without in situ annealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…[4] [7] [16] Jamison et al, reported a process flow consisting of a P V D step followed by a RT A annealing at 750 o C, which showed promise in eliminating the interlayer completely with careful control of the anneal times and oxygen flow concentration, as shown in Figure 9. [31] P V D and annealing in presence of O 2 may prove useful as described in the next section. [31] However, it must be noted that due to incomplete data, no conclusion can be drawn on the mechanism at work.…”
Section: Structural Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] [7] [16] Jamison et al, reported a process flow consisting of a P V D step followed by a RT A annealing at 750 o C, which showed promise in eliminating the interlayer completely with careful control of the anneal times and oxygen flow concentration, as shown in Figure 9. [31] P V D and annealing in presence of O 2 may prove useful as described in the next section. [31] However, it must be noted that due to incomplete data, no conclusion can be drawn on the mechanism at work.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…[31] P V D and annealing in presence of O 2 may prove useful as described in the next section. [31] However, it must be noted that due to incomplete data, no conclusion can be drawn on the mechanism at work. [8] A safe bet for the mechanism of formation at the interlayer is that, most substrates are not free of native oxide.…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also evident that a high‐field‐induced vertical onset is exhibited at mole fraction of 0.45. Therefore, to assess the HD‐GSLP TFET for symmetrical voltage operations between 1.0 V ≤ V DD ≤ 0.5 V, a physical gate oxide of 2.5 nm ( ε = 22) is assumed keeping in consideration the physically demonstrated ultra‐thin EOTs as low as 0.3 nm 31 and particularly the successful physical demonstration of HfO 2 thin films of 2.5 nm through processes like cyclic physical vapor Hf deposition (PVD) 32 or atomic layer deposition (ALD) followed by rapid thermal crystallization 33 . Moreover, gate tunnel leakage current usually dominates for physical oxide thicknesses lesser than 2 nm 34 .…”
Section: Device Structure and Simulation Setupmentioning
confidence: 99%
“…HfO 2 has received considerable attention because it possesses excellent scalability along with a big dielectric permittivity (κ) value (>20), a relatively large band gap of 5.8 eV, and compatibility with the conventional transistor process . Industries are converging to integrate the HfO 2 ‐based high‐k gate dielectrics in advanced transistor applications . However, one of the major concerns for application of the HfO 2 dielectrics gate stack in the device is its reliability.…”
Section: Introductionmentioning
confidence: 99%